2010
DOI: 10.1113/jphysiol.2009.186577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substitution of Cx43 by Cx32 on myocardial energy metabolism, tolerance to ischaemia and preconditioning protection

Abstract: Connexin 43 (Cx43) plays an important role in cardioprotective signalling by mechanisms at least in part independent of gap junctional communication. To investigate whether this role is related to specific properties of this connexin isoform, we used a knock-in mouse model in which the coding region of Cx43 is replaced by that of Cx32. Homozygous Cx43KI32 mice showed reduced cell-to-cell Lucifer Yellow transfer (P < 0.01), but QRS duration and left ventricular fractional shortening (echocardiography) were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 36 publications
4
48
1
Order By: Relevance
“…Similar results have also been described in transgenic mice models [15,16]. Remarkably, whereas all these studies addressed the role of connexins forming gap junctions, none of them excludes the possibility that these effects were due to actions on unapposed Hc.…”
Section: Introductionsupporting
confidence: 72%
“…Similar results have also been described in transgenic mice models [15,16]. Remarkably, whereas all these studies addressed the role of connexins forming gap junctions, none of them excludes the possibility that these effects were due to actions on unapposed Hc.…”
Section: Introductionsupporting
confidence: 72%
“…Since ATP depletion was not necessarily associated with ventricular dysfunction depending on the animal model [45], the threshold of ATP level that affects diastolic function might vary according to the status of SERCA2a. In a previous study, we showed that SERCA2a protein expression was reduced by endoplasmic reticulum (ER) stress-mediated degradation in OLETF at 25-30 weeks of age, when significant changes in ryanodine receptor 2 and phospholamban were not observed [10].…”
Section: Susceptibility Of Diastolic Function To Atp Depletionmentioning
confidence: 99%
“…In this ROS formation and spreading may play an important role the presence of connexin 43 (Cx43) in the mitochondrial inner membrane [17,62,84,160,182,184] (see also below).…”
Section: Ischemic Preconditioning a Brief Synopsismentioning
confidence: 99%
“…In fact, it has been demonstrated that Diazoxide (a drug supposed to cause protection by increasing ROS production through actions on mK ATP channels) may induce both pre-and postconditioning protection [62,84,160]. However, replacement of Cx43 by Cx32 in mice is characterized by loss of preconditioning protection, in particular when induced by Diazoxide [184]. Moreover, the failure of cardiomyocytes from Cx43 +/-mice to be protected by Diazoxide, has been attributed to the attenuated ROS generation [84].…”
Section: Summary Of Redox-stress and Redox-signaling In The Context Omentioning
confidence: 99%